2005
DOI: 10.1111/j.1462-5822.2005.00548.x
|View full text |Cite
|
Sign up to set email alerts
|

Global epithelial cell transcriptional responses reveal Streptococcus pyogenes Fas regulator activity association with bacterial aggressiveness

Abstract: SummaryThe bacterial human pathogen Streptococcus pyogenes (group A streptococci, GAS) is able to adhere to, internalize into and cross-talk on multiple levels with its host cells. To gain insight into the Fas function in pathogenesis we used Affymetrix human genome DNA-arrays to measure temporal and global transcriptional responses of HEp-2 cells infected with M49 S. pyogenes wild-type bacteria and D D D D fas X, an isogenic S. pyogenes two-component-signal-transduction system mutant. A modified stringent sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
65
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(73 citation statements)
references
References 45 publications
6
65
2
Order By: Relevance
“…68 Klenk et al 68 observed increased abundance of transcripts for CSF2, CXCL1, CXCL2, CXCL3, CCL20, IL6 and IL8, as well as transcription factors Jun and FosB. They also observed stimulation of release of IFNγ, corroborating for another Gram positive bacterial species the release of IFNγ by epithelial cells of the wet mucosa.…”
Section: Methodsmentioning
confidence: 57%
“…68 Klenk et al 68 observed increased abundance of transcripts for CSF2, CXCL1, CXCL2, CXCL3, CCL20, IL6 and IL8, as well as transcription factors Jun and FosB. They also observed stimulation of release of IFNγ, corroborating for another Gram positive bacterial species the release of IFNγ by epithelial cells of the wet mucosa.…”
Section: Methodsmentioning
confidence: 57%
“…42,48 The positive effect of FasX on streptokinase activity was also reported in a strain of M1T1 serotype (MGAS2221). 18 In host response studies performed with strain CS101, FasX was shown to control positively the interaction of S. pyogenes with laryngeal cells by affecting adherence and internalization rates, massive cytokine gene transcription and release, host cell apoptosis via a caspase-2 activation pathway and cytotoxicity.…”
Section: Integration Of Srnas Into the Regulatory Network Of Streptomentioning
confidence: 99%
“…18 In host response studies performed with strain CS101, FasX was shown to control positively the interaction of S. pyogenes with laryngeal cells by affecting adherence and internalization rates, massive cytokine gene transcription and release, host cell apoptosis via a caspase-2 activation pathway and cytotoxicity. 48 The authors of the study suggested that by mediating these functions FasX may influence local tissue destruction and general bacterial aggressiveness towards epithelial cells during the infection process. 48 In Streptococcus dysgalactiae subsp.…”
Section: Integration Of Srnas Into the Regulatory Network Of Streptomentioning
confidence: 99%
See 1 more Smart Citation
“…Apoptosis in streptococcal pathogenesis is affected by interacting factors including, context of infection (Marriott and Dockrell, 2006), cells undergoing apoptosis (Kobayashi et al, 2003;Nakagawa et al, 2004;Miyoshi-Akiyama et al, 2005), for example, apoptosis aids in the clearing of infection if macrophages are undergoing apoptosis, while it would be harmful to the host if lymphocytes are undergoing apoptosis. Other factors include, whether the bacteria is internalized or extracellular (Cywes Bentley et al, 2005) and accordingly the type of apoptosis pathways activated (Klenk et al, 2005). In our murine GAS sepsis model, we have measured expression levels in whole spleens, which involved the response of various cells including macrophages, T and B lymphocytes, dendritic and endothelial cells etc.…”
Section: Discussionmentioning
confidence: 99%